2017
DOI: 10.1038/srep46396
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography to Estimate Retinal Blood Flow in Eyes with Retinitis Pigmentosa

Abstract: Ophthalmologists sometimes face difficulties in identifying the origin of visual acuity (VA) loss in a retinitis pigmentosa (RP) patient, particularly before cataract surgery: cataract or the retinal disease state. Therefore, it is important to identify the significant factors correlating with VA. Nowadays, retinal blood flow in superficial and deep layers can be estimated non-invasively using optical coherence tomography angiography (OCTA). We estimated blood flow per retinal layer by using OCTA; investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 28 publications
7
66
2
Order By: Relevance
“…Further research in patients with BCD at various stages is necessary to clarify when the deficit in blood flow to the choriocapillaris commences. We could not investigate the study parameters in 17% of eyes; however, this rate is similar to that reported previously for OCTA with the same Avanti system in patients with RP (38%) 15. The low image quality is due to poor fixation in patients with BCD and RP with low visual function.…”
Section: Discussionsupporting
confidence: 60%
“…Further research in patients with BCD at various stages is necessary to clarify when the deficit in blood flow to the choriocapillaris commences. We could not investigate the study parameters in 17% of eyes; however, this rate is similar to that reported previously for OCTA with the same Avanti system in patients with RP (38%) 15. The low image quality is due to poor fixation in patients with BCD and RP with low visual function.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, the clarity of the images of the choroidal vascular layer was dependent on the status of the RPE, which was affected by the stage of RP. 8 In addition to the original images, binarized images and skeletonized images were obtained by the Angio Exerciser software, which was provided by Zeiss for research purposes only. The perfusion density (PD) was calculated as the percentage of the area occupied by vessels in the designated 3 3 3-mm area based on the binarized images.…”
Section: 13mentioning
confidence: 99%
“…A quantitative analysis also found a significant reduction in superficial and deep vascular density among RP patients, and an enlargement of FAZ when compared to the normal controls (Sugahara et al. ). However, no study so far has reported the comparison between OCTA and CDFI methods.…”
Section: Discussionmentioning
confidence: 94%
“…; Sugahara et al. ). However, no study so far has reported the comparison between the two methods and the relationship between the changes in retinal large vessels and terminal vessels.…”
Section: Introductionmentioning
confidence: 96%